Synthesis, transport properties and electronic structure of p-type Cu1+xMn2−xInTe4 (x = 0, 0.2, 0.3). Issue 7 (4th February 2020) - Hobbis, Dean; Shi, Wencong; Popescu, Adrian; Wei, Kaya; Baumbach, Ryan E.; Wang, Hsin; Woods, Lilia M.; Nolas, George S.
Abstract : The synthesis, electronic structure and temperature dependent transport properties of polycrystalline Cu1+ x Mn2− x InTe4 ( x = 0, 0.2, 0.3) are reported for the first time. Abstract : The synthesis, electronic structure and temperature dependent transport properties of polycrystalline Cu1+ x Mn2− x InTe4 ( x = 0, 0.2, 0.3) are reported for the first time. These quaternary chalcogenides were synthesized by direct reaction of the elements, followed by solid state annealing and hot press densification. The thermal conductivity is low for all specimens and intrinsic to the material system. Furthermore, the off-stoichiometry specimens illustrate the sensitivity of the transport properties to stoichiometry, with a greater than two-orders-of magnitude increase in carrier concentration with increased Cu content. First principles calculations of the electronic structure are also reported, and are in agreement with the experimental data. This fundamental investigation shows the potential towards further optimization of the electrical properties that, in addition to the intrinsically low thermal conductivity, provides a basis for further research into the viability of this material system for potential energy-related applications.